Low-Voltage CMOS Operational Amplifiers Theory, Design and Implementation - Sakurai, Satoshi; Ismail, Mohammed (The Springer International Series in Engineering and Computer Science, Analog Circuits and Signal Processing, 1995)
Low-Voltage CMOS Operational Amplifiers: Theory, Design and Implementation discusses both single and two-stage architectures. Opamps with constant-gm input stage are designed and their excellent performance over the rail-to-rail input common mode range is demonstrated. The first set of CMOS constant-gm input stages was introduced by a group from Technische Universiteit, Delft and Universiteit Twente, the Netherlands. These earlier versions of circuits are discussed, along with new circuits developed at the Ohio State University. The design, fabrication (MOSIS Tiny Chips), and characterization of the new circuits are now complete. Basic analog integrated circuit design concepts should be understood in order to fully appreciate the work presented. However, the topics are presented in a logical order and the circuits are explained in great detail, so that Low-Voltage CMOS Operational Amplifiers can be read and enjoyed by those without much experience in analog circuit design. It is an invaluable reference book, and may be used as a text for advanced courses on the subject